Degradation kinetics in corn silage under different packing densities and storage times - Casillas-Gómez, Christian Humberto (2026)
Introduction. Forage compaction and storage time are determining factors in the fermentation and preservation of corn silage. Objective. To evaluate the effect of different compaction densities and storage times on the nutritional quality, degradation kinetics, and in vitro digestibility of neutral detergent fiber and dry matter of corn silage. Materials and methods. The study was conducted in Tepatitlán, Jalisco, Mexico, in June 2015. Corn plants were harvested 120 days post-planting to prepare minisilos, which were opened 30 days later. A completely randomized design with a 5 × 5 factorial arrangement was used, and the factors were compaction density (450, 600, 750, 900, and 1050 kg DM m-3) and storage time (30, 60, 90, 120, and 150 days). Results. The 600 kg DM m-3 treatment at day 90 showed the best NDF digestibility (87.9 %; p < 0.05). In the ruminal degradation kinetics, fraction a was higher (p < 0.05) in the treatment of 1050 kg DM m-3 at day 120, where the pH was lower. However, fraction b and the degradation rates of both fractions (ca and cb) did not show differences between treatments (p > 0.05). The increase in compaction density maintained optimal pH levels for longer storage times. Nevertheless, the excessive increase in compaction density (from 900 to 1050 kg DM m-3), combined with a prolonged storage time, negatively affected the in vitro digestibility of neutral detergent fiber. Conclusions. Compaction density and storage time affected the chemical composition and in vitro digestibility of neutral detergent fiber in corn silage; however, their effect on degradation kinetics was inconsistent.